ANALYSIS OF THE INFLUENCE OF SHIP SCHEDULING, GUIDELINE SERVICES, WEATHER, AND LOADING EQUIPMENT READINESS ON SHIP WAITING TIME IN PORT - Nawawi, Cholis Imam; Anwar, Syairi; Supriatiningsih, Tuti; Purnaningratri, Indah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2022)
The purpose of this study was to determine the effect of ship scheduling factors, guide service, weather, and the readiness of loading and unloading equipment on the ship‘s waiting time at the port. This type of research is descriptive and quantitative, conducting field research through observation and interviews to obtain research data. This research was conducted on officers at the port of Merak. The sampling technique in this study was random sampling, with a sample size of 100 ship officers at the Merak port. The results showed that ship scheduling had a significant positive effect on ship waiting time, guide services had a significant positive effect on ship waiting time, the weather had a significant positive effect on ship waiting time.